Characteristics and Antibacterial Activity of Apis and Trigona Honey Types against Escherichia coli and Staphylococcus Aureus on Various Heating - La Ode Sumarlin; Nurul Amilia; Anna Muawanah; Nadya Uswatun Hasanah; Hajar Hajar (Syarif Hidayatullah State Islamic University, 2022)
Heating in honey processing can inhibit fermentation, crystallization, and the growth of microorganisms, such as bacteria. However, the effect of the honey heating process on the properties of honey and its antibacterial activity has not been further studied. Therefore, in this study, the properties of honey of both Apis and Trigona species from Bogor, Kalimantan, Sulawesi, Sumatra, and Lombok, were tested. The properties of honey, including water content, acidity, reducing sugar, 5-hydroxymethylfurfural (HMF), and diastase enzyme activity, were tested at heating temperatures 50, 70, and 90 °C. The antibacterial activity was determined using the disc method against Escherichia coli and Staphylococcus aureus. The results showed that the average water content and acidity values decreased after heating. However, the values met the SNI quality requirements with a water content value of < 22% and the acidity value not exceeding 50 mL NaOH 0.1 N/kg in the Apis and Trigona types of honey. The reduced sugar content fluctuated after heating all samples, and the average HMF level of honey increased after heating. However, the activity of the diastase enzyme decreased, although the value was still within the SNI standard value. The selected honey samples of the Apis and Trigona types were active in inhibiting the growth of Staphylococcus aureus but were not active against Escherichia coli.